MicroRNA‐181a regulates the activation of the NLRP3 inflammatory pathway by targeting MEK1 in THP‐1 macrophages stimulated by ox‐LDL. Issue 8 (2nd April 2019) - Song, Jinyang; Yang, Shaonan; Yin, Ruihua; Xiao, Qi; Ma, Aijun; Pan, Xudong
Abstract: Atherosclerosis (AS) is a chronic inflammatory disease that is characterized by the deposition of lipids in the vascular wall and the formation of foam cells. Macrophages play a critical role in the development of this chronic inflammation. An increasing amount of research shows that microRNAs affect many steps of inflammation. The goal of our study was to investigate the regulatory effect of miR‐181a on the NLRP3 inflammasome pathway and explore its possible mechanism. Compared with the control group, the expression of miR‐181a was downregulated in the carotid tissue of AS group mice, while the expression of MEK1 and NLRP3‐related proteins was upregulated significantly. In vitro, when THP‐1 macrophages were stimulated with oxidized low‐density lipoprotein (ox‐LDL), the expression of miR‐181a was decreased, the MEK/ERK/NF‐κB inflammatory pathways were activated and the expression of NLRP3 inflammasome‐related proteins was upregulated. Exogenous overexpression of miR‐181a downregulated the activation of the MEK/ERK/NF‐κB pathway and decreased the expression of NLRP3 inflammasome‐related proteins (such as NLRP3, caspase‐1, interleukin‐18 [IL‐18], IL‐1β, etc). Exogenous miR‐181a knockdown showed the opposite results to those of overexpression group. A luciferase reporter assay proved that miR‐181a inhibited the expression of MEK1 by binding to its 3′‐untranslated region. When we knocked down miR‐181a and then treated cells with U0126 before ox‐LDL stimulation, we found that U0126 reversed the increased activation of the MEK/ERK/NF‐κB pathway and upregulation of NLRP3 inflammasome‐related proteins (NLRP3, caspase‐1, IL‐18, IL‐1β) that resulted from miR‐181a knockdown. Our study suggests that miR‐181a regulates the activation of the NLRP3 inflammatory pathway by altering the activity of the MEK/ERK/NF‐κB pathway via targeting of MEK1. Abstract : miR‐181a expression was decreased and the expressions of MEK1 and NLRP3‐related inflammatory factors were upregulated in the mice carotid atherosclerotic plaque tissues and in oxidized low‐density lipoprotein stimulated THP‐1 macrophages. miR‐181a regulates the activation of the NLRP3 inflammatory pathway by altering the activity of the MEK/ERK/NF‐κB pathway via targeting of MEK1 in THP‐1 macrophages.